Genetics A Molecular Approach - Brown, Terence A (Taylor & Francis Group, 2005)
The text explains the basic principles of molecular biology and genetics and is ideal for modern introductory courses in these subjects. The book begins by describing the molecular nature of the gene before discussing genetic analysis in detail.